2013
DOI: 10.5194/acp-13-7451-2013
|View full text |Cite
|
Sign up to set email alerts
|

European atmosphere in 2050, a regional air quality and climate perspective under CMIP5 scenarios

Abstract: To quantify changes in air pollution over Europe at the 2050 horizon, we designed a comprehensive modelling system that captures the external factors considered to be most relevant, and that relies on up-to-date and consistent sets of air pollution and climate policy scenarios. Global and regional climate as well as global chemistry simulations are based on the recent representative concentration pathways (RCP) produced for the Fifth Assessment Report (AR5) of the IPCC (Intergovernmental Panel on Climate Chang… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 69 publications
3
64
0
10
Order By: Relevance
“…It is recognized that climate change may also have some influence on future PM 2.5 concentrations in the UK; however the focus is here on UK precursor emission sensitivity and many studies have concluded that on the 2030 timescale air pollutant concentrations will be much more strongly influenced by changes in precursor emissions than by changes in climate (e.g. Langner et al, 2012;Coleman et al, 2013;Colette et al, 2013).…”
Section: Vieno Et Al: the Sensitivities Of Emissions Reductions Fmentioning
confidence: 99%
“…It is recognized that climate change may also have some influence on future PM 2.5 concentrations in the UK; however the focus is here on UK precursor emission sensitivity and many studies have concluded that on the 2030 timescale air pollutant concentrations will be much more strongly influenced by changes in precursor emissions than by changes in climate (e.g. Langner et al, 2012;Coleman et al, 2013;Colette et al, 2013).…”
Section: Vieno Et Al: the Sensitivities Of Emissions Reductions Fmentioning
confidence: 99%
“…Existing investigations all agree on a larger impact of air quality policies (Tagaris et al, 2007;Hedegaard et al, 2013;Colette et al, 2013), supporting the efficiency of currently planned mitigation strategies, despite external penalties brought about by climate change and long-range transport.…”
Section: Impacts Of Climate Changementioning
confidence: 99%
“…The impact of model horizontal resolution on simulated O 3 concentrations has been primarily linked to less dilution of emissions when using a finer resolution (Valari and Menut, 2008;Tie et al, 2010;Colette et al, 2013;Stock et al, 2014;Schaap et al, 2015). Investigating the impact of increasing model horizontal resolution from 48 to 6 km on O 3 concentrations in Paris, Valari and Menut (2008) found modelled surface O 3 to be more sensitive to the resolution of input emissions than to meteorology.…”
Section: Introductionmentioning
confidence: 99%
“…Markakis et al, 2015;Schaap et al, 2015;Yu et al, 2016;Neal et al, 2017). Although the same model processes are represented at different model resolutions, simulated pollutant concentrations can vary due to differences in (i) the resolution of emissions, which may have a nonlinear effect on the chemical formation of pollutants, and (ii) the resolution of the driving meteorology (Valari and Menut, 2008;Tie et al, 2010;Arunachalam et al, 2011;Colette et al, 2013;Markakis et al, 2015;Schaap et al, 2015).…”
Section: Introductionmentioning
confidence: 99%